2015
DOI: 10.1007/s10147-015-0857-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of preoperative performance status and hemoglobin concentration to predict overall survival for patients aged ≥75 years after radical cystectomy for treatment of bladder cancer

Abstract: ECOG PS and preoperative Hb concentration were useful for prediction of clinical outcome after RC for elderly patients. This information may aid decision-making in the treatment of elderly patients with MIBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Overall and cancer-specific survival outcomes following radical cystectomy have remained unaltered over the last three decades, with 5-yr overall survival between 50% and 60% [17,19,35]. Numerous studies have confirmed the association between comorbidity status and survival outcomes following radical cystectomy [9,10,17,19,3646]. However, no comorbidity index has demonstrated superiority in predicting survival outcomes.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Overall and cancer-specific survival outcomes following radical cystectomy have remained unaltered over the last three decades, with 5-yr overall survival between 50% and 60% [17,19,35]. Numerous studies have confirmed the association between comorbidity status and survival outcomes following radical cystectomy [9,10,17,19,3646]. However, no comorbidity index has demonstrated superiority in predicting survival outcomes.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Both of these conditions are considered risk factors of post-radical cystectomy complications [20][21][22][23]. Surprisingly, low haemoglobin concentration was found to be predictor of radical cystectomy in the current cohort, despite elsewhere demonstrated negative impact on postoperative survival [24,25]. An analysis of the SEER database by Canter et al revealed that less than 5% of patients with high-grade T1 disease underwent immediate cystectomy.…”
Section: Discussionmentioning
confidence: 87%
“…Consistently, Hara et al. 25 had emphasized the usefulness of ECOG score in predicting clinical outcome after radical cystectomy for elderly patients. Moreover, multivariate analysis indicated surgical procedure was independent prognostic factor for PFS in UCB patient.…”
Section: Discussionmentioning
confidence: 99%